Service Quality from Patients Perspective between Normal Delivery and Cesarean Section - Yassin Oki Purbayanto; Ari Natalia Probandari; Zulaika Nur Afifah (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Introduction: The differences of indication, procedures, and post delivered care between normal delivery and cesarean section are estimated to make a difference in service quality from patients perspective. This study aimed to compare service quality from patients perspective on normal delivery and cesarean section in PKU Muhammadiyah Surakarta Hospital. Method: This research used an observational analytic study with cross sectional approach. Minimum respondents amount (n=100) were calculated based on Cohen, Manion, and Morrison table. Respondents were recruited from Annisa ward in PKU Muhammadiyah Surakarta Hospital and only 97 respondents were participated and appropriated with restricion criteria during Desember 2015 until January 2016. Service quality from patients perspective measured by Quality Impact score (QI). Service quality from patients perspective as dependent variable and delivery methods as independent variable were analyzed using Mann Whitney. Result: There was no significance difference of service quality between normal delivery and cesarean section (p=0.064)based on Mann Whitney result. Conclusion: There was no significance difference of service quality between normal delivery and cesarean section in PKU Muhammadiyah Surakarta Hospital. Keywords: service quality from patients perspective, normal delivery, cesarean section